ANALISIS INTERVENSI KENAIKAN HARGA BBM BERSUBSIDI PADA DATA INFLASI KOTA SEMARANG - Novia Dian Ariyani; Triastuti Wuryandari; Yuciana Wilandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Intervention model is a model of time series data analysis that originally used to explore impact of unexpectedly external events to the observation variable. In this study, an increases subsidized fuel price analysis has done in June 2013 (first step function) and November 2014 (second step function) for Semarang inflation data at January 2007 until January 2015 and purposed to obtain the intervention model and forecast the Semarang inflation for some time later. Based on the result of inflated subsidized fuel price analysis for Semarang inflation data, the resulted model is ARIMA (1,0,0) with first intervention order b = 1, s = 2, r = 0 and second intervention order b = 1, s = 1, r = 0. Furthermore, the model is used to forecast inflation in Semarang for forward some periods.Keywords: ARIMA, intervention analysis, step function, inflation, subsidized fuel.